PENGENALAN TEHNIK SADARI DI RT 15 KELURAHAN BULURAN KENALI - Nurfitriani Nurfitriani; Julaecha Julaecha (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Breast cancer is still a big problem in Indonesia, since 68.6% of women with breast cancer treatment kedokter disease on local advanced stage (IIIa and IIIb), while in the early stages (I and II) only 22.4%. High number of incident breast cancer this should be a concern for the Government and society in General.The purpose of the realize is to know early detection/as the presence of breast cancer that can be performed in women of fertile age. It turns out that 75-82% of breast malignancy found upon inspection SADARI and can lower the mortality rate to 20%.The purpose of outreach/health education was SADARI this was aimed at the citizens of RT 15 Kelurahan Buluran get familiar with the hope of providing information and can be applied directly to the mothers in order to detect early cancer occurrence in order to be able to be treated as early as possible and can decrease the number of pain or death in women.Methods of implementation with discussion, faqs, provide leaflets and demonstrations as well as do SADARI engineering examination. After the execution of counseling health with mom mother on RT 10 and 15 have learned techniques SADARI and can practice breast self examination so that treatment can be optimal.The effort can be done one of them keep diet, eating instant foods, food ingredients that contain MSG, can also do a breast exam alone or commonly abbreviated to realize.